Prussian blue analogues derived iron-cobalt alloy embedded in nitrogen-doped porous carbon nanofibers for efficient oxygen reduction reaction in both alkaline and acidic solutions - Yin, D.; Han, C.; Bo, X.; Liu, Jian; Guo, L. (Academic Press, 2019)
© 2018 Elsevier Inc. Exploring highly active, inexpensive and robust electrocatalysts for oxygen reduction reaction (ORR) is of great significance as a competitive alternative to noble metal-based catalysts in energy conversion and storage devices. In the present study, we design a novel ORR electrocatalyst of iron-cobalt (FeCo) alloy nanoparticles embedded on N-doped porous carbon nanofibers (FeCo@PCNF-T) by electrospinning of [Polyacrylonitrile (PAN)/Prussian blue analogues/CaCO3] and post-calcination treatment. The obtained catalysts with bimetallic active sites show unique three-dimensional (3D) hierarchical meso/macropores structures. FeCo alloy nanoparticles are encapsulated into graphitic carbon that can increase stability and provide additional catalytic active sites. Under the optimized condition, FeCo@PCNF-800 displays excellent ORR electrocatalytic activity in alkaline solutions, with a more positive half-wave potential (E1/2of 0.854 V vs RHE) and larger limited-diffusion current density (j of 6.012 mA cm-2) than those of 20 wt% Pt/C (E1/2of 0.849 V and j of 5.710 mA cm-2). In addition, FeCo@PCNF-800 also exhibits comparable ORR electrocatalytic activity in acidic solutions to those of 20 wt% Pt/C with onset potential and half-wave potential as more positive as 0.843 V vs RHE and 0.739 V vs RHE, respectively. Moreover, FeCo@PCNF-800 exhibits excellent tolerance towards methanol, stability and a four-electron pathway in both basic and acidic solutions. The excellent ORR electrocatalytic activity performance of FeCo@PCNF-800 is attributed to the synergistic effect of the FeCo alloy nanoparticles and N-doped porous carbon nanofibers. The synergistic effect can improve the mass and charge transport capability and increase active sites of FeCo-N-C. Furthermore, this work offers a new insight for the reasonable design and development of efficient non-noble metal electrocatalysts for challenging electrochemical energy-related technologies.